Population genetics of atta sexdens rubropilosa (hymenoptera: formicidae) (2013)
The genetic variability of Atta sexdens rubropilosa leaf-cutting ants collected from five brazilian localities was evaluated with PCR-RAPD technique. We used 15 primers producing 148 fragments of which 123 (83,11 %) contained polymorphisms. The estimated Shannon index was 0.3836 ± 0.2335 showing that these ants possess high genetic diversity. The GST value was 0,2372 and PT = 0,184, indicating that the analyzed populations are moderately differentiated and 82 % of the variation obtained occur within populations. Although Mantel’s test had shown correlation between genetic distances and geographic was observed that Ivatuba and Itambé (33,8 km) have the small geographical distance and the largest genetic distance. The lower genetic distance was estimated for Maringá and Ivatuba but this localities have a small geographic distance (42,3 km), indicating that there are no barriers for mating among reproducers in these populations. The high degree of polymorphism (83,11 %) and the ability to cross among the populations in the studied regions indicate that this species of leaf-cutting ant is well adapted to the region; therefore, integrated control programs can be developed.